Determinants of capital adequacy ratio on banking industry: Evidence in Indonesia Stock Exchange - Bahtiar Usman; Henny Setyo Lestari; Tiara Puspa (Jurnal Keuangan dan Perbankan, 2019)
Capital adequacy ratio (CAR) is an important indicator of bank safety sustainability. Banks that can guarantee CAR means the bank has the power to resist the financial crisis, protecting the bank itself and funds from depositors. This study aimed to determine the factors that affect the CAR. The sample used in this study is the banking industry listed on the Indonesia Stock Exchange (IDX) from 2007 until 2018. Independent variables are bank size, leverage, loan loss reserves, net interest margin, loan assets ratio, and liquidity. The dependent variable is CAR. The number of samples is 27 conventional banks by using purposive sampling. By using panel data regression analysis by estimating ordinary General Least Squares (GLS) method. The results of this study indicate that bank size, leverage, loan loss reserve, net interest margin, and loan asset ratio has an effect on CAR significantly while liquidity has no effect on CAR. The results of this study are expected to be used as a reference for bank managers and investors in looking at the factors that affect the CAR in the banking industry.JEL Classification: C33, G21, G30DOI: https://doi.org/10.26905/jkdp.v23i3.2981